Pengaruh Reward dan Punishment Terhadap Kinerja Pegawai Pada Balai Besar Meteorologi Klimatologi dan Geofisika Wilayah II Tangerang Selatan - Ella Purwati; Lili Sularmi (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of reward and punishment on employee performance at Balai Besar Meteorologi Klimatologi dan Geofisika Wilyah II Tangerang Selatan. The method used is quantitative. The population of this study were 80 employees at the South Tangerang Meteorology, Climatology and Geophysics Agency and 80 employees were taken as samples using saturated samples. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are that reward has a significant effect on employee performance with a coefficient of determination of 53.3% and the hypothesis test is obtained t value > t table or (9,440 > 1,990). Punishment has a significant effect on employee performance with a coefficient of determination of 50.4% and the hypothesis test is obtained t count > t table or (8,905 > 1,990). Reward and punishmnet simultaneously have a significant effect on employee performance with the regression equation Y = 16,695 + 0,333X1 + 0,230 X2. The correlation coefficient is 0,776 and the coefficient of determination is 60.2% while the remaining 39.8% is influenced by other factors. Hypothesis testing obtained F value > F table or (58,255 > 3,115).